Particulate Matter Pollution in Urban Cities of India During Unusually Restricted Anthropogenic Activities - Yadav, Ravi; Vyas, Pushpendra; Kumar, Praveen; Sahu, Lokesh Kumar; Pandya, Umangkumar; Tripathi, Nidhi; Gupta, Mansi; Singh, Vikram; Dave, Pragnesh N.; Rathore, Devendra Singh; Beig, Gufran; Jaaffrey, S. N. A. (Frontiers in Sustainable Cities, 2022)
The outbreak of COVID-19 is a global public health challenge and has affected many countries, including India. The nationwide lockdown was imposed in India from March 25 to May 31, 2020 to prevent the transmission of COVID-19. The study intends to assess the impact of the absence of major anthropogenic activities during the various phases of the COVID-19 lockdown (LDN) period on the daily mean concentrations of PM2.5 and PM10 in six populated cities of Jaipur, Jodhpur, Kota, Udaipur, Ajmer, and Alwar in the state of Rajasthan. Investigation has been done for the different periods, including the pre-lockdown—PRELD (January 1–March 4, 2020), partial lockdown—PLDN (March 5–24, 2020), COVID-19 lockdown—LDN (March 25–May 31, 2020), and unlocking—ULC (June 1–August 31, 2020) phases. We have also compared the mean concentrations of PM2.5 and PM10 with the same period of the year 2019. A significant improvement in air quality during the COVID-19 LDN period was noticed in all cities compared to 2019 and for the same period of the year 2020. However, the levels of PM2.5 and PM10 were seen to rise during the second, third, and fourth LDN phases compared to the first LDN, indicating that the subsequent lockdowns started with some relaxations and dusty conditions. On the other hand, wind-blown dust is another vital source of PM10, resulting in high concentrations in the summer months (April–May). Significant reductions in PM2.5 ( 25–50%) and PM10 (20–37%) in all six cities during the LDN period compared with PRELD were estimated. However, with significant variations from city to city, the lowest reductions in PM2.5 ( 25%) and PM10 ( 20%) were measured in Jodhpur and Ajmer, respectively. It was noticed that the episodes of rainfall and transport of oceanic air masses resulted in a reduction of particles during the ULC period compared to the LDN period. The air quality index was, more or less, in the “good to satisfactory” category during the first 3 LDN periods, whereas it was moderate for Jodhpur, Jaipur, and Ajmer during the last LDN period. The study will be helpful to determine mitigation policies to minimize air pollution, especially in developing regions.